LEGAL ADMISSION OF LEGAL SOCIETY CONDUCTING THE NATIONAL PARK OF KAYAN MENTARANG (TNKM) - Marthin Marthin; Wiwin Dwi Ratna; Yasser Arafat; Afdhal . (Universitas Borneo Tarakan, 2020)
ABSTRACT The Kayan Mentarang National Park (KNPM) area located in the Heart of Borneo (HoB) in North Kalimantan lives various Dayak sub-tribes. They inhabit and keep the forest so that the forest remains safe and sustainable. Indigenous and tribal peoples who have customary forest areas in which their status of appointment as KMNP initially may receive, so that the process can continue in the inaugural process. But with the development of information and circumstances the situation was changed and now the indigenous people reject the pegat which will be doneThe legal issues that serve as the purpose of this paper are: the recognition of traditional rights of indigenous and tribal communities and the recognition of local wisdom in the management of Kayan Mentarang National Park. Using the normative juridical and customary law approaches that this method is expected to address the issue of law.The dynamics of the development of society and law can change the legal status of both government and customary law community to a legal fact. Forests as natural resources and the environment are constitutionally the government's obligation to regulate them. Inauguration of customary forest as a national park brings legal consequences to rights and obligations. Implementation of laws and regulations is limited by Human Rights. It is necessary to harmonize the law, so that both the interests of indigenous and tribal peoples, as the inhabitants as well as the natural resources, the environment, and the biodiversity as the interests of mankind are not mutually harmful. Keywords: Customary Law Community, Traditional Rights, National Park